GATES AUTO DOOR CAR WITH LIGHTS MODULATED - Lina Carolina; Luyung Dinani, Skom, MMSi (Jurnal Sistem Komputer, 2002)
In scientific writing wi ll be explained about automatic gates with modulated headlights, where to find the car lights were adjusted by the relative frequency darker because of this background that the author alleviate human task in performing daily activities by using an automatic gate with the car lights modulated.